2009
DOI: 10.1016/j.tcs.2009.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Finding Paths between graph colourings: PSPACE-completeness and superpolynomial distances

Abstract: a b s t r a c tSuppose we are given a graph G together with two proper vertex k-colourings of G, α and β. How easily can we decide whether it is possible to transform α into β by recolouring vertices of G one at a time, making sure we always have a proper k-colouring of G? This decision problem is trivial for k = 2, and decidable in polynomial time for k = 3. Here we prove it is PSPACE-complete for all k ≥ 4. In particular, we prove that the problem remains PSPACE-complete for bipartite graphs, as well as for:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 134 publications
(137 citation statements)
references
References 9 publications
(23 reference statements)
2
134
0
Order By: Relevance
“…See [4,8,9] for some examples. Computational work has focused on deciding whether there is a path in the reconfiguration graph between a given pair of colorings [5,10,14]. Other structural considerations of the reconfiguration graph have also been investigated in [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…See [4,8,9] for some examples. Computational work has focused on deciding whether there is a path in the reconfiguration graph between a given pair of colorings [5,10,14]. Other structural considerations of the reconfiguration graph have also been investigated in [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Polynomial-time reachability algorithms have been developed for tractable source problems such as 2-COLORING [31][32][33], MATCHING [4], MINIMUM SPANNING TREE [4], and 2-SATISFIABILITY [34]. Reachability has been shown to be PSPACE-complete for many NP-complete source problems, such as CLIQUE [4], 4-COLORING [35], INDEPENDENT SET [4,17], 3-SATISFIABILITY [34], VERTEX COVER [4], DOMINATING SET [4], LIST EDGE-COLORING [36], LIST L(2, 1)-LABELING [37], INTEGER PROGRAMMING [4], STEINER TREE [38], and SET COVER [4].…”
Section: Tools For Proving the Complexity Of Reachabilitymentioning
confidence: 99%
“…For k = 3, it was shown that the diameter is in O(|V(G)| 2 ) for each connected component (and that this bound is tight, as there exist configurations at distance Ω(|V(G)| 2 )), and that both reachability and shortest transformation can be solved in polynomial time [32]. In contrast, for k ≥ 4, there are both yes-instances and no-instances for connectivity [31], and there exists a family of graphs and a k ≥ 4 such that for every graph in the family there exist components of diameter superpolynomial in |V(G)| [35]. Moreover, for k ≥ 4, reachability is strongly NP-hard [79] and PSPACE-complete, even for bipartite graphs, planar graphs for 4 ≤ k ≤ 6, and bipartite planar graphs for k = 4 [35].…”
Section: K-coloring Reconfigurationmentioning
confidence: 99%
See 2 more Smart Citations